A (in)efetividade dos direitos fundamentais no Estado Democrático de Direito: as ações afirmativas como consectárias da busca da eficaz aplicação do princípio constitucional da igualdade - Schneider, Yuri (Universidade do Vale do Rio do Sinos, 2007)
This research has, as a goal, to make evident that the affirmative action is an important instrument to the fulfillment of a material or substantial equality, in a state that is passing through many crisis in its structure. With the analysis comes a study about the current crisis, fundamental rights to human dignity, with a special focus in the fundamental right to equality, passing to a direct approach to the affirmative action. With this, hopes to demonstrate that the fundamental rights may come in the form of constitutional principles or rules, and that the equality, as a first dimension fundamental right, cannot be understood by a purely formal subjective logic, inherent to liberalism. The conclusion is that it’s necessary that the State abandons a position of neutrality, which has a well proved insufficiency, and start to promote an material-objective equality, that can be achieved with the use of affirmative actions
Keywords: 1988; ação afirmativa; Brasil; dignidade humana; direito constitucional; igualdade; princípio; direitos humanos; affirmative action; equality principle; fundamental rights; crisis of the state; Ciências Sociais Aplicadas